Pediatric drug development in China: Reforms and challenges. (October 2019) - Wu, Weijia; Tang, Zhijia; Chen, Jiyuan; Gao, Yuan
Graphical abstract: Caption: China faces many challenges in pediatric drug development. To solve these problems, China launched a series of policies to promote development of pediatric medicines that have resulted in positive consequences within past 8 years. However, there is still much room for improvement, especially in the establishment of regulatory frameworks with economic incentives and mandatory requirements. Abstract: In China, child and adolescent pediatricians often face challenges in treating children with the appropriate medications. Within the last 8 years, the Chinese government has already initiated a series of policies to promote development of age-appropriate medicines for children. In this study, we introduced the current status of pediatric drugs, obstacles for pediatric drugs development and regulatory reforms in China. The lack of label information in drugs for children, inadequacy of age-appropriate dosage forms and strengths, and shortage of pediatric drugs are some of the problems commonly faced. There exists neither mandatory requirements nor enough financial drivers for development of pediatric medicines. Though some progress in terms of pediatric drugs development as well as distribution have been made by Chinese government over past years, further efforts are necessary to improve availability of pediatric medications.